Микола Бабак: штрихи до портрету сучасника - Спіркіна, О.О. (Чорноморський літопис, 2011)
Розглянуто життєвий та творчий шлях відомого українського художника, письменника та колекціонера Миколи Бабака. Особливо підкреслено патріотизм митця, його любов до рідного краю, історичної спадщини нашого народу, традицій та звичаїв українців. Показано неймовірну працьовитість і талант представника черкаської творчої інтелігенції. Рассмотрен жизненный и творческий путь известного украинского художника, писателя и коллекционера Николая Бабака. Особенно подчеркнуто патриотизм мастера, его любовь к родному краю, историческому наследию нашего народа, традициям и обычаям украинцев. Показано невероятное трудолюбие и талант представителя черкасской творческой интеллигенции. It is devoted to the course of life and the career of the well-known Ukrainian artist, writer and collector Mykola Babak. Especially it is underlined the master’s patriotism, his love to the native land, the historical heritage of our nation, the Ukrainians’ traditions and customs. It is shown the unbelievable zeal and talent of the representative of the Cherkasy creative intelligentsia.
Keywords: artist, writer, collector, historical heritage, traditions and customs, creative.